2020
DOI: 10.1177/1357633x20938919
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation and costs of telepsychiatry programmes: A systematic review

Abstract: Objective Telepsychiatry involves use of telecommunications technology to deliver psychiatric care and offers promise to reduce costs and increase access to mental health services. This systematic review examined cost reporting of telepsychiatry programmes for mental healthcare. Methods We systematically searched electronic databases for studies reporting costs, including economic evaluations such as cost-effectiveness analyses, or costs of developing telepsychiatry programmes for clinical care of mental disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 63 publications
(122 reference statements)
1
36
0
2
Order By: Relevance
“…While maintenance of improvements was found at follow up assessments in two reviews regarding video-based tele-therapy (27, 34) and another regarding telephone-based therapy (24), two other reviews reported that videoconference interventions may show less longevity in maintenance of effects than face-to-face interventions (26, 31). A final review of mixed modality remote interventions suggested that while inferior to face to face formats at shorter term follow up, remote interventions may be more beneficial than face-to-face at longer follow-ups (36 months) (18). Further details on clinical outcomes are available in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While maintenance of improvements was found at follow up assessments in two reviews regarding video-based tele-therapy (27, 34) and another regarding telephone-based therapy (24), two other reviews reported that videoconference interventions may show less longevity in maintenance of effects than face-to-face interventions (26, 31). A final review of mixed modality remote interventions suggested that while inferior to face to face formats at shorter term follow up, remote interventions may be more beneficial than face-to-face at longer follow-ups (36 months) (18). Further details on clinical outcomes are available in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Two reviews presented conclusions regarding the economic impact of telepsychiatry (32, 36). One review concluded that tele-psychiatry can be cost effective, compared to face-to-face interventions, particularly in rural areas where the number of consultations required before telepsychiatry becomes more cost effective (combatting initial equipment costs) is lower (32).…”
Section: Resultsmentioning
confidence: 99%
“…However, conclusions were similar across reviews, and no review had all the same studies contributing to any synthesis. Multimedia Appendix 2 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]38, and Multimedia Appendix 3 present further details of the study overlap.…”
Section: Overviewmentioning
confidence: 99%
“…A total of 2 reviews presented conclusions regarding the economic impact of telepsychiatry [29,33]. One review concluded that telepsychiatry can be cost-effective as compared with face-to-face interventions, particularly in rural areas where there were lower numbers of consultations required before telepsychiatry becomes more cost-effective (combatting initial equipment costs) [29].…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…52 In a systematic review on the cost-effectiveness of telepsychiatry services, it was observed that in 60% of the reports, the service was economical. 53 Another study report telepsychiatry to be cost-effective in chronic conditions needing rehabilitation in older adults. [53][54][55] A cost-effectiveness study reports that telepsychiatry practice was 50 times more economical than visiting a distant tertiary care center and four times more economical than a community outreach service.…”
Section: Cost-effectiveness and Rural Practicementioning
confidence: 99%